2014
DOI: 10.1080/00107530.2014.880314
|View full text |Cite
|
Sign up to set email alerts
|

When Is Transference Work Useful in Psychodynamic Psychotherapy? Main Results of the First Experimental Study of Transference Work (FEST)

Abstract: This article presents the main results of the First Experimental Study of Transference (FEST). The background of the study, as well as the aims, main hypotheses, and methods are described. The participants were 100 patients who were randomized to psychodynamic psychotherapy of one year's duration, with transference work or without transference work. The analyses of the effects of psychodynamic psychotherapy with transference work versus psychodynamic psychotherapy without transference work are presented. The t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Fifth, we could assess the outcome only in terms of problem levels. However, the psychodynamic technique may be related to other mechanisms, such as affect regulation, tolerance, and insight, which may have roles in symptom reduction [ 53 ]. Moreover, long-term follow-up is necessary because the literature suggests that the effects of psychodynamic treatments increase during follow-up [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fifth, we could assess the outcome only in terms of problem levels. However, the psychodynamic technique may be related to other mechanisms, such as affect regulation, tolerance, and insight, which may have roles in symptom reduction [ 53 ]. Moreover, long-term follow-up is necessary because the literature suggests that the effects of psychodynamic treatments increase during follow-up [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…The therapists experienced it as superfluous to use TI in therapy with adolescents that were relatively high-functioning or had no personality pathology. Higher relational functioning might suggest that less is activated in the transference [ 26 , 27 , 28 , 30 ]. Research on adults indicates that moderate levels of TI can be useful in therapy with patients who have personality problems, as well as those who have serious and chronic difficulty in establishing stable and meaningful relations.…”
Section: Discussionmentioning
confidence: 99%
“…Systematic research on specific interventions in psychodynamic therapy with adults has revealed that some patients profit more from working with transference than others according to various patient characteristics [ 26 , 27 , 28 , 29 , 30 ]. Transference interventions (TI) seem to have specific positive effects on long-term functioning in patients with personality problems, as well as serious and chronic difficulties in establishing stable and meaningful relations [ 26 , 27 , 28 , 30 ]. Patients with higher relational functioning seem to benefit from low to moderate levels of TI, but they have difficulty with high levels of TI [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Transference can also act as a form of resistance and as an obstacle to treatment by keeping the patient from feeling like they can discuss certain ideas or topics, or a strong negative transference can make it hard for the patient to attend sessions regularly or even cause them to terminate the treatment (for an overview of the different effects of transference and ways of working with it, see Fink, 1997 ; Corradi, 2006 ; and Fink, 2007 , esp. chapter 7; for empirical studies of its usefulness, see Marmarosh, 2012 ; Hersoug et al, 2014 ; Suszek et al, 2015 ; Ulberg et al, 2021 ).…”
Section: The Concept Of Transference In Psychotherapymentioning
confidence: 99%